Pengaruh Teknologi Informasi, Kemampuan Pengguna Dan Budaya Organisasi Terhadap Kualitas Sistem Informasi Akuntansi (Studi Kasus Pada Badan Keuangan Dan Aset Daerah Kabupaten Bandung Barat) - Adi Rachmanto; Yogi Riyan Aditama (Journal of Economics, Management, Business and Accounting (JEMBA), 2022)
This study aims to determine information technology, ability of users and organizational culture to the quality of accounting information systems. The questionnaires were distributed as many as 30 questionnaires and all of them were re-entered in data processing. The method used in this research is descriptive and verification method with a quantitative approach. The source of data in this study is primary data with data collection techniques carried out by surveys using questionnaires. The analytical method used in this research is Structural Equation Modeling (SEM) through Partial Least Square (PLS) approach using SmartPLS 2.0 software. The results of this study indicate that Information Technology, Ability of Users and Organizational Culture affect the Quality of Accounting Information Systems.